Incidence of complications in patients of Plasmodium vivax malaria at a tertiary center in Northwest India - Nagarwal, Amitesh; Meena, P. D. (International Journal of Advances in Medicine, 2019)
Background: Malaria is a protozoal disease caused by infection with parasites of Plasmodium species, such as P. vivax, P. falciparum, P. malariae, P. ovale and P. knowlesi through female Anopheles mosquito. Plasmodium vivax alone causes 60 to 65% of infections in India. The main objective of the study was to observe various complications in the patients affected with P. vivax malaria and to analyse the clinical, hematological and biochemical profile of these patients. Methods: A non-randomized prospective study was carried out on 170 patients with acute febrile illness admitted in the department of Medicine, SMS Hospital, Jaipur during period from October 2011 to September 2012 presented The infection was confirmed by detection of parasite (for P. vivax) in peripheral blood film by thick and thin slide methods and rapid diagnostic test (Optimal test). Results: Male preponderance was seen in the study. Death was noted in 5 (3%) patients. Thrombocytopenia (85%) was the most common finding observed. Level of serum creatinine was more than 1.5 mg/dl in 34.7% patients. Thirty-one patients (18.23%) had severe anaemia (Hb <6 gm/dl). Severe hypoglycemia was observed in 19 patients (<40-60 mg/dl). Acute renal failure was common comorbidity observed in majority of the patients. Mean LDH value was significantly higher in patients with hepatitis and anemia. Conclusions: The clinical pattern of P. vivax monoinfection has changed recently. Every patient of P. vivax malaria should be evaluated thoroughly for clinical or biochemical evidence of any complications and patients presenting with complications should managed as per guidelines of severe malaria.